Factors influencing healthcare providers' behaviours in deprescribing: a cross-sectional study - Chee Tao Chang; Huan-Keat Chan; Ewilly Jie Ying Liew; Muhammad Radzi Abu Hassan; Jason Choong Yin Lee; Wee Kooi Cheah; Xin Jie Lim; Philip Rajan; Siew Li Teoh; Shaun Wen Huey Lee (Taylor & Francis Group, 2024)
Introduction: Deprescribing serves as a pivotal measure to mitigate the drug-related problem due to polypharmacy. This study aimed to map the factors influencing healthcare providers' deprescribing decision using the Behaviour Change Wheel framework and develop an innovative conceptual model to support deprescribing practice.Methods: A cross-sectional online survey targeting doctors and pharmacists was conducted to assess the influence of various factors on healthcare providers' comfort in recommending deprescribing. The conceptual model was formulated, based on the existing deprescribing framework and the Behaviour Change Wheel. The model's robustness was scrutinised through Partial Least Squares Structural Equation Modeling (PLS-SEM), and model-fitting indices were employed to obtain the best-fit model.Results: A total of 736 responses were analysed with the final best-fit model consisting of 24 items in 5 constructs (R2: 0.163; SRMR: 0.064; rho_c: 0.750-0.862; AVE: 0.509-0.627) and three independent factors. Based on the results, we proposed that deprescribing could be promoted through strategies aimed at enhancing healthcare providers internal capabilities such as knowledge levels, when patients' condition deteriorated and previous experiences with adverse events of drugs. Organisational support in providing such educational opportunities is important, with the empowerment of patient and healthcare providers through policy enhancements, guideline development, and effective communication.Conclusion: The deprescribing behaviours of healthcare professionals are influenced by an intricate interplay of patient, prescriber, and system factors. Enhancing deprescribing practices necessitates a comprehensive strategy that encompasses providers and patients' education, the development of structured deprescribing guidelines, the implementation of deprescribing support tools, and the enhancement of communication between healthcare providers.